2018
DOI: 10.1103/physrevb.98.054432
|View full text |Cite
|
Sign up to set email alerts
|

Majorana corner modes in a second-order Kitaev spin liquid

Abstract: Higher-order topological insulators are distinguished by the existence of topologically protected modes with codimension two or higher. Here, we report the manifestation of a second-order topological insulator in a two dimensional frustrated quantum magnet, which exhibits topological corner modes. Our exactly-solvable model is a generalization of the Kitaev honeycomb model to the Shastry-Sutherland lattice that, besides a chiral spin liquid phase, exhibits a gapped spin liquid with Majorana corner modes, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 55 publications
0
38
0
Order By: Relevance
“…In terms of second-order TSCs in 2D, the MZMs will emerge at its corners i.e., Majorana corner states (MCSs), which are localized at the intersection of two gapped topologically distinct edges. The study of MCSs is still at a very exploratory stage, and a few works are recently reported: high-temperature Majorana Kramers pairs with time-reversal symmetry localized at corners [42][43][44], MCSs in a p-wave superconductor with an inplane external magnetic field [45], Majorana bound states (MBSs) in a second-order Kitaev spin liquid [46], as well as 2D and 3D second-order TSCs with (p+ip) and (p+id) superconductors [47].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of second-order TSCs in 2D, the MZMs will emerge at its corners i.e., Majorana corner states (MCSs), which are localized at the intersection of two gapped topologically distinct edges. The study of MCSs is still at a very exploratory stage, and a few works are recently reported: high-temperature Majorana Kramers pairs with time-reversal symmetry localized at corners [42][43][44], MCSs in a p-wave superconductor with an inplane external magnetic field [45], Majorana bound states (MBSs) in a second-order Kitaev spin liquid [46], as well as 2D and 3D second-order TSCs with (p+ip) and (p+id) superconductors [47].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the appearance of the local magnetization is ubiquitous in the Kitaev-type models. Needless to say, in many models, various kinds of topological boundary states such as chiral edge modes [32] and corner modes [40] have been found to appear.…”
Section: B Comparison With Related Workmentioning
confidence: 99%
“…Higher-order topological phases have been studied in systems protected by order-two symmetries (e.g., reflection and inversion symmetry [22][23][24][26][27][28]), rotational invariance [25,29,30], and combinations of the above [31][32][33]. Gapless hinge and corner excitations may also appear in interacting models [34,35], Floquet phases [36,37] and can coexist with gapless surface states [38]. Higher-order topology does not necessarily rely on an underlying regular lattice, but can be also found in quasicrystals respecting certain spatial symmetries [39,40].…”
Section: Introductionmentioning
confidence: 99%